ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KONSUMSI MASYARAKAT DI KECAMATAN ENDE TENGAH KABUPATEN ENDE - Sry Dewi Yanti; Yustina Penu (JURNAL EQUILIBRIUM, 2021)
Consumption is the total expenditure to obtain goods and services in an economy within a certain period. Consumption expenditure is a major component of Gross National Product, therefore the main attention needs to be paid attention to and focused on the analysis of the factors that determine consumption expenditure. This study aims to analyze the effect of income levels, interest rates and inflation. This study uses multiple linear regression analysis tools. The results of the multiple regression research show that there is an influence of the income level, interest rate and inflation variables on the consumption level in Ende Tengah District, Ende Regency. The results of the t test showed that the variable value of the income level was -0.840 and the significance was 0.555, the variable value of the interest rate was -0.649 and significant 0.633 and the inflation variable value was 1.066 and significant 0.480. The results of the F test were obtained at 0.794 and 0.657 significant. The t-test result of inflation has a significant effect on the level of consumption and the contribution of the independent variable to the dependent variable (Y) is 70.4%. The suggestion that the government of Ende Regency can take is to pay more attention to the level of income because the income set by the government also affects the level of consumption. For this reason, the income determination policy must be carried out and the income level increased according to the needs of life.